Teacher Well-Being—A Conceptual Systematic Review (2020–2023) - Laura Maria Kurrle; Julia Warwas (Education Sciences)
Teacher well-being (TWB) is increasingly recognized as being influential on educational outcomes, teacher retention, and overall school performance. However, despite a growing body of empirical research, TWB remains conceptually ambiguous, with multiple, often conflicting definitions and models, which hinders the comparability of findings. The essential question (What are the conceptual models of TWB that form the basis of studies?) is answered with a Conceptual Systematic Review (CSR), analyzing 168 recent publications, to synthesize the usage and frequency of TWB-related terms. The CSR identifies three perspectives—Conditions, Components, and Outcomes—each comprising multiple categories and subcategories that often show overlaps or inconsistencies. Our review reveals that within a widely shared notion of TWB as a psychological construct with positive cognitive and affective connotations, certain sets of factors, in particular individual factors such as beliefs/evaluations and emotions/affect, are proposed as conditions in some studies and as components in other studies. These results call for clearer distinctions between TWB’s constitutive elements and its (hypothetically) determining elements. By offering a systematic framework for understanding and sorting research on TWB, the reported review provides a foundation for future studies. Ultimately, a precise conceptualization could inform future interventions and policies aiming to foster TWB.